Stern men - Gilbert, Elizabeth; Chalmers, Anne (New York Penguin Boos, 2000)
A wonderful First novel about life, love, and lobster fishing... high entertainment
American corner
The first New York Times bestelling author of eat, pray, love
11
Keywords: English fiction